Impact du changement d'usage des sols sur la biodiversite: consequences sur l'erosion des sols - Jouquet, P.; Podwojewski, Pascal; Bottinelli, N.; Mathieu, J.; Orange, Didier; Tran, D. T.; Valentin, Christian (2007)
This study deals with the influence of land use change on earthworm diversity on the one hand and the consequences of these modifications on soil erosion on the other hand. This work has been realized in the Northern Vietnam, in the Dong Cao experimental watershed (average slope ~40%). Our work shows that endogeic earthworms are associated to agrosystems with low vegetation cover (or low litter content) while agrosystems with high vegetation cover are characterized by anecic earthworms that create casts on the soil surface. The quantity of soil accumulated on the soil surface by earthworms can be very important (10-20kg m-?). A simulation of water runoff associated to the annual measurement of soil erosion from 1m? plots shows that casts deposited on the soil surface lead to a better infiltration of water but do not increase soil erosion. This study highlights that other biological factors than the vegetation must be considered for a sustainable management of steep slope agro-ecosystems in the Northern Vietnam.